Mineral composition of bread wheat lines with introgressions of alien genetic material - O. A. Orlovskaya; S. I. Vakula; L. V. Khotyleva; A. V. Kilchevsky (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Modern bread wheat (Triticum aestivum L.) cultivars developed mainly to increase productivity often contain low concentrations of minerals in their grain. Wild and primitive wheats demonstrate rich genetic diversity, including the content of minerals in the grain, and can be used to improve the wheat gene pool for this trait. The aim of this work was to study the mineral composition in the grain of bread wheat lines with introgressions of the genetic material from Triticum L. spp.Materials and methods. We studied parental spring bread wheat cultivars, accessions of tetraploid and hexaploid Triticum spp., and 20 introgressive lines obtained on their basis in 2018 and 2020. Concentrations of macro- (K, P, Ca, and Mg) and micronutrients (Zn, Fe, Cu, and Mn) were measured using atomic emission spectrometry with inductively coupled plasma, and total protein content in wheat grain according to GOST 10846-91. The data were processed using the Statistica 10.0 and MS Excel software packages.Results and conclusion. The content of minerals in the grain of Triticum spp. was higher than in T. aestivum cultivars (the twoyear average difference was 1,02 to 2,13-fold, depending on the studied mineral). Most of the lines with alien genetic material exceeded their parent bread wheat cultivars in Zn, Fe, Cu and Mn content and came close to them in the levels of N, P, Mg and K. ANOVA established a statistically significant impact of the genotype, environment, and genotype × environment interaction on the variation of the grain macro- and micronutrient content. Lines with a consistently high concentration of grain minerals and high productivity were identified. These lines are of interest for wheat breeding for grain quality.